HIV-1 BF intersubtype recombinant Vpu second alpha helix plays an important role in the viral release and BST-2 degradation - de Candia, Cristian Ariel (2013)
We previously reported a naturally occurring BF intersubtype recombinant Vpu variant with augmented capacity to enhance viral replication. Structural analysis of this variant revealed that its transmembrane domain (TMD) and α-helix I in the cytoplasmic domain (CTD) corresponded to subtype B, whereas CTD α-helix II corresponded to subtype F1. This work was aimed at evaluating the role of Vpu CTD α-helix II domain on viral release enhancement and down-modulation of BST-2 and CD4 from cell surface. In addition, as serine residues in either Vpu amino acid positions 61 or 64 have been shown to regulate Vpu intracellular half-life, which in turn could influence the magnitude of viral release, we also studied the impact of these residues in the BF Vpu functions, since S61 and S64 are infrequently found among BF recombinant Vpu variants. Our results showed that interchange of Vpu α-helix II between subtypes (B→F) directly correlated with enhancement of viral release and, to a lesser extent, with changes in the capacity to down-modulate BST-2 and CD4 of the resulting chimera. No statistical differences on viral release and BST-2 down-modulation were observed between Vpu BF and VpuBF E61S. On the other hand, VpuBF A64S showed a slightly reduced capacity to enhance viral production but was modestly more efficient than VpuBF in down-modulating BST-2. In summary, our observations clearly evidence that α-helix II is actively involved in Vpu viral release-promoting activity, and that intersubtype recombination between subtypes B and F1 originated a protein variant with higher potential to boost the spread of the recombinant strain that harbors it.